1954
DOI: 10.1002/hlca.19540370139
|View full text |Cite
|
Sign up to set email alerts
|

Über eine biologische Bedeutung der Gallenfarbstoffe. Bilirubin und Biliverdin als Antioxydantien für das Vitamin A und die essentiellen Fettsäuren

Abstract: catkgorie de solutions. On Btablit sur la droite s1 ( fig. 3) la position du point R, (solution saturBe de D5-1-10 exempte de phosphate monocalcique appartenant it la catBgorie sl).Dans la construction auxiliaire ( fig. 3), on dispose ainsi de deux points (R, e t S,') it l'aide desquels on peut tracer la droite gr.On mkne par le point R, une droite parallkle it gl. Le point d'interscction de cette droite g, avec la ligne h, est le point X,' qui fournit les coordonnBes fx,' et dxi de la solution X, cherchke.2. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

1975
1975
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(17 citation statements)
references
References 2 publications
0
17
0
Order By: Relevance
“…Bilirubin was only recently recognized as a potentially important anti-oxidant of physiological significance (Stocker et al, 1987), although this property had already been known for some time (Bernard et al, 1954). Administration of bilirubin demonstrated to be cytoprotective in models of ischemic heart injury and oxidative damage Clark et al, 2000).…”
Section: Recent Insights In Heme Oxygenase and A Novel Role For Hementioning
confidence: 99%
“…Bilirubin was only recently recognized as a potentially important anti-oxidant of physiological significance (Stocker et al, 1987), although this property had already been known for some time (Bernard et al, 1954). Administration of bilirubin demonstrated to be cytoprotective in models of ischemic heart injury and oxidative damage Clark et al, 2000).…”
Section: Recent Insights In Heme Oxygenase and A Novel Role For Hementioning
confidence: 99%
“…Abnormally high plasma concentrations are associated with the risk of developing neurologic dysfunction due to preferential deposition of bilirubin in brain and its toxic effects on cell functions. In fact for many years, biliverdin and bilirubin were generally regarded as waste products of heme metabolism in higher animals, although earlier work suggested that these bile pigments might play a role as natural antioxidants, since small quantities of the pigment stabilize vitamin A and ␤-carotene during intestinal uptake, and animals with low plasma bilirubin showed early signs of vitamin E deficiency (4,5).…”
mentioning
confidence: 99%
“…Some earlier and neglected work has also suggested that bilirubin might play a role as an antioxidant (9)(10)(11). Indeed, reactions of bilirubin involving free radicals (12,13) or toxic oxygen reduction products are well documented in the literature: unconjugated bilirubin scavenges singlet oxygen with high efficiency (14), reacts with superoxide anion (15) and peroxyl radicals (7), and serves as a reducing substrate for peroxidases in the presence of hydrogen peroxide or organic hydroperoxides (16,17).…”
mentioning
confidence: 99%